PENGARUH PEMBELAJARAN IPS TERHADAP SIKAP EMPATI DAN SIKAP TANGGUNG JAWAB SISWA KELAS VIII DI MTSN GRESIK - Anis Fitriyah; Hayyun Lathifaty Yasri (STKIP Singkawang, 2024)
This research is motivated by social problems that are still evident in students who are unable to feel and understand the feelings of their friends, ostracizing friends who have problems, mocking their teacher's physical appearance and comparing it to something else, students' inattention towards the teacher when the learning process is taking place, and neglecting tasks that need to be completed. These actions are indicators of students' lack of empathy and responsibility attitudes. This study aims to: (1) determine the influence of social studies learning on the empathy attitudes of eighth-grade students at MTsN Gresik, (2) determine the influence of social studies learning on the responsibility attitudes of eighth-grade students at MTsN Gresik, and (3) determine the influence of social studies learning on the empathy attitudes and responsibility attitudes of eighth-grade students at MTsN Gresik. The approach used in this research is a quantitative approach with correlational research type. Data collection techniques were conducted using questionnaires and documentation. The population used was all eighth-grade students at MTsN Gresik with a total of 360 students and using simple random sampling technique with 189 samples. Data analysis techniques were conducted using simple linear regression analysis, multivariate analysis, and t-test. Based on the data analysis, it can be concluded that (1) there is an influence of social studies learning on empathy attitudes by 23.3%, while the remaining 76.7% is influenced by other variables, (2) there is an influence of social studies learning on responsibility attitudes by 28.1%, while the remaining 71.9% is influenced by other variables, (3) there is an influence of social studies learning on students' empathy attitudes and responsibility attitudes, the MANOVA output shows a p-value/significance value of 0.000 < 0.05, meaning H0 is rejected and Ha is accepted.